PEMANFAATAN ELECTRONIC COMMERCE BERBASIS ANDROID UNTUK MININGKATKAN PENJUALAN PADA TOKO DEWI - Sisi Dwi Lestari (Jurnal Signaling, 2019)
Dewi Shop is an online business that sells clothes. Many ways done in doing business Goddess Store one of them by using social media on smartphone. The transaction process using this social media in value is still less effective due to limited info, and ordering manually so that it will slow down the transaction process and the possibility of errors. These problems can be solved by making mobile commerce applications that can directly view and conduct product ordering transactions. Mobile commerce is a development of e-commerce so that transaction process services or goods can use mobile devices. Currently the most popular smartphone device is Android Smartphone. Android is an information system that uses an open source linux kernel that uses java as a programming language making it easier for developers to create apps on android. The writer in this research will design and make android application as ordering media at Dewi Shop by using data collection method, and application development method.